Каноническое право как правовая система - Оборотов, Ігор Гариславович; Оборотов, Игорь Гариславович; Oborotov, Igor' (My University, 2012)
The article analyzes the canonical (ecclesiastical) law and the recognition of its postulated an independent legal system, of a personal nature. Investigation of the structure of Canons and legal system and imposing it on a theoretical model of the structure of the legal system can satisfy itself that the canon law of all the necessary features of the legal system. Analysis of the subject and methods of a canon law regulation is used to refer to the specifics of canon law.
Оборотов И. Г. Каноническое право как правовая система / И. Г. Оборотов // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 272-281.
Keywords: каноническое право; правовая система; канонико-правовая жизнь; канонико-правовое регулирование; акривия; икономия; канонічне право; правова система; каноніко-правове життя; каноніко-правове регулювання; акривія; ікономия; canon law; legal system; canonical and legal life; canon law regulation; akribeia; oeconomy